Lambego Language Phonological Interference in Usage Indonesian Language for Students of SMPN 3 Pasimarannu Lambego Village, Pasimarannu District Selayar District - Muhammad Dahlan; Hanana Muliana (Universitas Muhammadiyah Enrekang, 2022)
The main problem in this study is the influence of the first and second languages into Indonesian on the denotation of phonemes and consonants. This study aims to determine the form of Lambego language interference, especially in the field of phonology in the use of Indonesian.This research is a descriptive research, this population is all students of class VII, VIII, IX SMPN 3 Pasimarannu. Total population of 58 people. Considering that the population is not too large, this research is a total sample. The data and data sources referred to in this study are phrases and sentences contained in the pronunciation of the Lambego language which have interference with the use of Indonesian, causing these vowel and consonant sounds. Data collection techniques use instruments in collecting research data in the form of verbal and nonverbal. The results of this study indicate that there is interference from Lambego language into Indonesian on verbal and nonverbal, with several groups of phonological changes namely: (1) reduction of consonant symbolism /?/ or also called interference reduction of consonant phoneme /k/, (2) reduction of phoneme symbolism / g/, (3) reduction of the denotation of the phoneme /n/, (4) reduction of the denotation of the phoneme /l/ and phoneme /h/, (5) replacement of the denotation of the phoneme /i/ to the phoneme /y/, (6) replacement of the denotation of the phoneme / é/ becomes the phoneme /o/, (7) replaces the symbol for phoneme /u/ to phoneme /o/, (8) replaces the symbol for phoneme /q/ to phoneme /k/ , (9) replaces the symbol for phoneme /z/ to /j /, (10) changing the symbol of phoneme /f/ to phoneme /p/, (11) changing the symbol of phoneme /b/ to phoneme /p/, (12) changing the symbol of phoneme /v/ to phoneme /b/.